COACHING PROGRAM DALAM MENINGKATKAN PENGEMBANGAN KARYAWAN PT HUTAMA KARYA INFRASTRUKTUR - Sudirja Sudirja; Ratih Setyo Rini (Sekolah Menengah Kejuruan (SMK) Pustek, 2022)
Human resource development must be carried out seriously and consistently, one of which is through coaching activities. Coaching is an HR development activity through internal qualitative actions, namely helping employees to identify their potential, goals in their careers, identify potential problems, and find ways to solve them, to get optimal performance. This research was conducted on employees of PT. Hutama Karya Infrastructure with a qualitative method. In collecting data, field observations were carried out through coaching activities. The analysis technique was carried out descriptively, namely explaining the actual conditions during the Coaching activity. The results of the activities carried out indicate that, employees of PT. Hutama Karya Infrastruktur gains self-reinforcement regarding its existence in the company, namely realizing career needs, occupying positions, and getting opportunities for self-development as well as increasing income / awards.